2015
DOI: 10.1177/0194599815572112
|View full text |Cite
|
Sign up to set email alerts
|

T1 Glottic Carcinoma

Abstract: ObjectiveRecent large-scale studies have observed differences in survival following treatment for early laryngeal carcinoma depending on treatment type but were not able to take sociodemographic, comorbidity, and facility data into account. The objective of this study was to determine whether survival differences across treatment types persist when these factors are included in the analysis.Study DesignRetrospective cohort analysis.SettingLinked Surveillance, Epidemiology, and End Results (SEER)–Medicare data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…While Chen et al included both open and endoscopic techniques in their evaluation, our study only included TLM and excluded for any other open partial surgical therapies. Though using Another recent study by Misono et al 22 looked at patients with T1 glottic lesions and concluded that those patients whose treatment included surgical therapy had better survival than those treated with XRT only. 22 This study utilized the surveillance, epidemiology, and end results (SEER) Medicare database that only includes patients with Medicare Part A and Part B, and only patients older than 66 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Chen et al included both open and endoscopic techniques in their evaluation, our study only included TLM and excluded for any other open partial surgical therapies. Though using Another recent study by Misono et al 22 looked at patients with T1 glottic lesions and concluded that those patients whose treatment included surgical therapy had better survival than those treated with XRT only. 22 This study utilized the surveillance, epidemiology, and end results (SEER) Medicare database that only includes patients with Medicare Part A and Part B, and only patients older than 66 years.…”
Section: Discussionmentioning
confidence: 99%
“…Though using Another recent study by Misono et al 22 looked at patients with T1 glottic lesions and concluded that those patients whose treatment included surgical therapy had better survival than those treated with XRT only. 22 This study utilized the surveillance, epidemiology, and end results (SEER) Medicare database that only includes patients with Medicare Part A and Part B, and only patients older than 66 years. In this patient group, these authors found that patients undergoing surgical excision or surgery plus XRT exhibited better overall survival compared with patients who were treated nonsurgically.…”
Section: Discussionmentioning
confidence: 99%